Legal Protection for Investors Buying and Selling Shares Online and in the Capital Market - Santika, Sela; Suyatno, Suyatno (Jurnal Multidisiplin Indonesia, 2024)
This study aims to know and analyze legal protection for investors in terms of buying and selling shares online and to find out and analyze the factors inhibiting the implementation of factors that hinder legal protection for investors in terms of buying and selling shares online. The research method carried out in this study is normative legal research, in this case, using material collection techniques in the form of document and literature studies. The results of this study show the form of legal protection for investors as consumers in Law Number 8 of 1999 concerning Consumer Protection, namely the establishment of BPKN and BPSK. Law Number 8 of 1995 concerning the Capital Market has been regulated regarding the disclosure of information that must be provided to investors, and the regulation of Bapepam-LK as a supervisory body for every activity related to the capital market, which has been transferred to the OJK. Law Number 21 of 2011 concerning the Financial Services Authority aspects of legal protection provided by this law are prevention or preventive efforts and enforcement or repression carried out by the Financial Services Authority. The inhibiting factors faced in carrying out investor protection are still the large number of unlicensed/illegal online stock investments and the lack of knowledge of the investor community related to illegal investments. Research Recommendations It is expected that the government will be able to update Law Number 8 of 1999 concerning Consumer Protection to protect consumers optimally in this era of highly developed technological development. It is expected that in the future, the government will need to regulate online stock investment through a special law. It is expected that in the future, there will be coordination and cooperation between OJK and BPKN / BPSK in ensuring investor (consumer) protection. Investors are expected to be more careful in seeking information and choosing a clear securities company that has obtained permission for its activities. To find out the forms of violations/crimes in capital market transactions and to know the legal protection of investors in capital market transactions. The journal writing method uses normative research with an approach, namely the statutory approach, namely Law Number 8 of 1995 concerning the capital market, the fact approach to alluding to capital practices in Indonesia, and the concept analysis approach to legal analysis. Based on the results of the study, namely: Legal Protection to the Capital Market Supervisory Body Article 4 of Law No. 8 of 1995 concerning the capital market stated that "coaching, regulating, supervising by Bapepam to create orderly, fair, and efficient capital market activities and crimes and violations in the capital market sector will be involved in legal cases, in capital market violations,  usually regarding BAPEPAM licensing and registration cases.